Using qualitative research in advertising : strategies, techniques, and applications - Morrison, Margaret A. (SAGE, 2012)
This second edition remains the only book to discuss both theory and application of qualitative research techniques to inspire great advertising and build strong brands. Using a step-by-step approach created for students considering advertising careers and for those currently working in the advertising industry, this book explains what qualitative research techniques are designed to do. The text describes how these techniques aid in uncovering insights useful for advertising strategy development, creative development, and post-campaign evaluation. Practical information and discussions on interviewing, projective techniques, focus groups, and online/social media applications positioned within a theoretical context illustrate the value of qualitative research in the real world